PENGARUH KEPUASAN KERJA, KOMPETENSI DAN DISIPLIN KERJA TERHADAP PRESTASI KERJA KARYAWAN BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) BHAKTI SUMEKAR SUMENEP - jurnalpps pps; Ahmad Halim Shidiq (Prodi Magister Manajemen Universitas Wijaya Putra, 2021)
This study is to determine and analyze the effect of both partially and simultaneously job satisfaction, competence, work discipline and have a significant and simultaneous effect on the work performance of the employees of the Sharia People's Financing Bank (PBRS) Bhakti Sumekar Sumenep. In addition, to analyze which variables among job satisfaction, competence, work discipline has a dominant effect on the work performance of the employees of the Sharia People's Financing Bank (PBRS) Bhakti Sumekar Sumenep. The approach in this research is quantitative by involving 150 employees as respondents. The results show that simultaneously, job satisfaction, competence and work discipline have a significant effect on the work performance of employees of the Sharia People's Financing Bank (PBRS) Bhakti Sumekar Sumenep. Partially job satisfaction, competence and work discipline have a significant effect on the work performance of employees of the Bhakti Sumekar Sumenep Islamic People's Financing Bank (PBRS). Competence has a dominant influence on the work performance of the employees of the Sharia People's Financing Bank (PBRS) Bhakti Sumekar Sumenep. Keywords: job satisfaction, competence, work discipline, work performance